DNA barcoding of dried seahorses illegally sold in Metropolitan Manila, Philippines, as Traditional Chinese Medicine (TCM) - Bueno, Kyara Patricia R.; Boleche, Glenn Raye P.; Cruz, Lucylle Jean A.; Geronimo, Anthony Justine C. (2024)
Seahorses are a member of the Family Sygnathidae and are found in tropical and temperate coastal regions with soft, sandy bottoms, among rocks and algae, and in lagoons with strong oceanic influences. Seahorses are among the most sought-after animals, commonly marketed as traditional Chinese medicine (TCM) used to treat various diseases. The trade of these species on a global scale caused a significant decline in their population and a negative impact on the marine ecosystem. All the existing seahorse species are now recorded under Appendix II of the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES). In the Philippines, these species are protected under the Philippine Fisheries Code (RA 8550), as amended by RA 10654, and the Philippine Wildlife Act (RA 9147). However, despite existing laws, the illegal trade of dried and live seahorses still persists. The study aims to identify seahorse species illegally traded in stores or markets in Metro Manila. A total of 22 whole-dried seahorses were purchased from different stores within Metro Manila. Nine specimens were bought from TCM stores in Binondo, Manila City, and 13 from aquatic pet shops in Cartimar Pet Center, Pasay City. Dried seahorse samples were subjected to morphological analysis and DNA barcoding. Morphological identification of all 22 samples revealed that four species of seahorses were sold in the said marketplaces. This includes Hippocampus kuda, Hippocampus comes, Hippocampus histrix, and Hippocampus kellogi. All samples underwent DNA extraction, amplification, and sequencing, with 15 sample sequences viable for BLAST and clustering analysis. Results of the clustering analysis revealed that 12 samples clustered under Hippocampus kuda, whereas the remaining three were under H. comes. Furthermore, results also showed that most of the seahorse species purchased in the three TCM stores and two aquatic pet shops were H. kuda, having a prevalence rate of 78% (TCM stores, Manila) and 62% (Cartimar Pet Center, Pasay), respectively. Thus, this study implies the persistent illegal selling of dried seahorses in the country, which calls for a more efficient, strict monitoring and effective policy implementation for the protection and conservation of seahorses and other marine wildlife.